Creation of Interactive Android Learning Media Articulate Storyline 3 on Fusion Food Material For Vocational School (SMK) on Temanggung - Gumilar, Mikhael Cahyo; Suryatna, Bambang Sugeng; Wahyuningsih, Wahyuningsih; Astuti, Pudji (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2025)
Learning in the modern era has a significant influence on student understanding. However, the use of conventional learning media is often less interesting, making students feel bored and less motivated, which ultimately reduces participation in learning activities. This study aims to develop more interesting interactive learning media and test its effect on student learning outcomes. This study uses a quantitative approach with the Research and Development (RD) method modified from the 4D model to 3D, including the Define, Design, and Development stages. The measuring instrument used is the t-test with the Liliefors model to determine the effect of interactive learning media based on Articulate Storyline 3 on student learning outcomes. Data were analyzed using normality tests, homogeneity tests, and paired t-tests. The results of the study indicate that the development of interactive learning media can be done through the Define, Design, and Development stages. In addition, it was found that interactive learning media based on Articulate Storyline 3 has a significant effect on improving student learning outcomes in Basic Culinary material, especially in the Fusion Food element. Thus, the use of interactive learning media has proven effective in increasing student engagement and understanding during learning activities. The results of the Pre Test and Post Test research were 45.53 and 76.73, with an increase in the Pre Test score which had an average of 45.53 which was lower than the Post Test score with an average of 76.73 so that in this study the use of interactive learning media Articulate Storyline 3 on Fusion Food material has an influence on student learning, so the use of this interactive learning media has an influence on Fusion Food learning activities for class X at SMK Swadaya Temanggung.